2017
DOI: 10.1021/acssuschemeng.7b00485
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Near Infrared Reflectance with Brilliant Yellow Hues in Scheelite Type Solid Solutions, (LiLaZn)1/3MoO4–BiVO4 for Energy Saving Products

Abstract: Enhanced near infrared (NIR) solar reflectance with interesting yellow hues in a new series of scheelite type solid solutions, [(LiLaZn) x/3Bi1–x ]­[Mo x V1–x ]­O4 (x = 0, 0.1, 0.2, 0.3, 0.4) were synthesized via conventional solid state reaction (SSR) method and planetary ball milling assisted solid state reaction (PBM) method. The structural, morphology, and reflectance (absorption) properties and coloring performance of the prepared compositions were analyzed by various advanced techniques. The solid soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Table lists the color coordinates and calculated total color difference (Δ E *) of all of the samples. Because Δ E * ≤ 5 units is considered good, the Δ E * values of all of the samples indicate that the synthesized pigments are chemically stable after the acid/alkali tests.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table lists the color coordinates and calculated total color difference (Δ E *) of all of the samples. Because Δ E * ≤ 5 units is considered good, the Δ E * values of all of the samples indicate that the synthesized pigments are chemically stable after the acid/alkali tests.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, the yellow pigments based on iron and tungsten codoped La 2 Ce 2 O 7 and BiVO 4 -coated mica–titanium oxide pigment have been reported. Notably, Rao et al also reported a suite of BiVO 4 -based brilliant yellow pigments and Y-doped Bi 2 MoO 6 yellow pigments, , which are friendly alternatives to toxic pigments (PbCrO 4 -based pigment and PbSbO 3 pigment). , These pigments with high near-infrared reflectance can serve as cold pigments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NIR solar reflectance could quantify the solar radiation and evaluate heat accumulation on the surface of materials. The NIR solar reflectance ( R *) of the samples distributed from 700 to 2500 nm were calculated as shown in the following formula where r (λ) is the experimentally measured spectral reflectance (W m –2 ) and i (λ) is the standard solar spectrum (W m –2 nm –1 ) obtained according to the standard of ASTM G173-03 , reference spectra.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, alkali rare earth bismolybdates of the type ARE­(MO 4 ) 2 with stable physical and chemical properties and high thermal stability have received extensive attention in the fields of electricity, light, catalysis, and magnetism. Rao et al synthesized a series of bright yellow pigments (LiLa) 1/2 MoO 4 –BiVO 4 and (LiLaZn) 1/3 MoO 4 –BiVO 4 by introducing alkali rare earth bimolybdates. , Table displays the previously reported studies on the improvement of optical properties based on bismuth vanadate. In tetragonal scheelite with a general formula of ABO 4 , various cations on the A site can be substituted to adjust the performance.…”
Section: Introductionmentioning
confidence: 99%